Degradação da resistência à corrosão de aços inoxidáveis duplex, devido ao envelhecimento em baixas temperaturas por tempos prolongados - Moreno, João Roberto Sartori (Universidade Federal de São Carlos, 2004)
Although duplex stainless steels exhibit good performance in many severe corrosive environments, their corrosion resistance can be hampered by precipitation of chromium (Cr) rich phases during aging heat treatments. Microstructural changes and corrosion behavior in two alloys with high and low content of chromium were investigated. Duplex stainless steels samples were aged at low temperatures (300°C and 400°C) for 3000, 5000 and 7000 hours. The changes at the microstructure were followed during the annealing time using an optical microscopy and measurements of phase percentages. Nanohardness was used in order to identify the phase responsible for the increasing in the global hardness. Immersion tests in ferric chloride cloreto férrico (FeCl3.6H2O 10%) and surface analysis by XPS were conducted intending to quantify the depletion in the corrosion resistance and identify the oxides presented in the surface oxide layer. G phase precipitation and α phase due to spinodal decomposition was identified by transmission electron microscopy. It was detected that the micro-structural changes affect the global properties, remarkably the global hardness and the corrosion resistance. TEM results showed that the Cr rich precipitation occurs manly in the ferritic phase. Spinodal decomposition and heterogeneous precipitation of G phase were found to be responsible for degradations of the corrosion properties. The results also showed a difference between the kinetics of precipitation of the lower Cr content sample and the higher Cr sample. The phenomena of precipitation and coalescence of Cr rich phases must be related with the increasing and decreasing tendencies of hardness, respectively and, inversely, the decreasing and increasing tendency of the resistance to localized corrosion and corrosion rates, which were determined by two electrochemical techniques (Tafel extrapolation and polarization resistance methods) and were compared with the rates determined by weight-loss measurements.
Degradation of the corrosion resistance of duplex stainless steel due to long aging at low temperatures
Keywords: Aço - corrosão; Filmes passivos; Aço inoxidável duplex; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA